ICT Update 73: e-agriculture strategies - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2013)
ICT Update is a bimonthly printed and on line magazine (http://ictupdate.cta.int) and an accompanying email newsletter published by CTA. This issue focuses on e-agriculture strategies.